Principles of Islamic law and the methods of interpretation of the texts (Uṣūl al-Fiqh), revised ed. - Kayadibi, Saim (Islamic Book Trust, 2018)
In the past couple decades, interest in learning and teaching Islamic law has increased in both the Muslim and non-Muslim world. The popularity of Islamic banking and finance has especially triggered scholarly studies in this field, since the study of uṣūl al-fiqh is the essence of comprehending the law revealed by the Lawgiver. In order to fully implement the intention of the Lawgiver in the field of tashrī‘, as well as in Islamic banking and finance, properly learning the components of uṣūl al-fiqh is highly essential for those who are both theorists and practitioners. A better understanding of the principles of Islamic law and the methods of interpretation of the texts is necessary to appropriately convey the message of the eternal sources to the experts, just as a driver’s licence is necessary to drive a car and a medical certificate is necessary to practice medicine − without these certificates, one may cause a serious accident or death. Such an understanding will protect students, especially those of the younger, technologically advanced generation, from reckless approaches towards aḥkām of the Qur’ān and the Sunnah. Studying the principles of Islamic law, uṣūl al-fiqh, is as essential as studying other sciences to be qualified in Islamic sciences, since they are a manifestation of divine law, which reflects the rules (aḥkām) derived from the main sources, the Qur’ān and the Sunnah, which are simply called the Sharī‘ah.